Subcortical Atrophy Is Associated with Cognitive Impairment in Mild Parkinson Disease: A Combined Investigation of Volumetric Changes, Cortical Thickness, and Vertex-Based Shape Analysis - Mak, E.; Bergsland, N.; Dwyer, M.G.; Zivadinov, R.; Kandiah, N. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: The involvement of subcortical deep gray matter and cortical thinning associated with mild Parkinson disease remains poorly understood. We assessed cortical thickness and subcortical volumes in patients with Parkinson disease without dementia and evaluated their associations with cognitive dysfunction. MATERIALS AND METHODS: The study included 90 patients with mild Parkinson disease without dementia. Neuropsychological assessments classified the sample into patients with mild cognitive impairment (n = 25) and patients without cognitive impairment (n = 65). Volumetric data for subcortical structures were obtained by using the FMRIB Integrated Registration and Segmentation Tool while whole-brain, gray and white matter volumes were estimated by using Structural Image Evaluation, with Normalization of Atrophy. Vertex-based shape analyses were performed to investigate shape differences in subcortical structures. Vertex-wise group differences in cortical thickness were also assessed. Volumetric comparisons between Parkinson disease with mild cognitive impairment and Parkinson disease with no cognitive impairment were performed by using ANCOVA. Associations of subcortical structures with both cognitive function and disease severity were assessed by using linear regression models. RESULTS: Compared with Parkinson disease with no cognitive impairment, Parkinson disease with mild cognitive impairment demonstrated reduced volumes of the thalamus (P = .03) and the nucleus accumbens (P = .04). Significant associations were found for the nucleus accumbens and putamen with performances on the attention/working memory domains (P < .05) and nucleus accumbens and language domains (P = .04). The 2 groups did not differ in measures of subcortical shape or in cortical thickness. CONCLUSIONS: Patients with Parkinson disease with mild cognitive impairment demonstrated reduced subcortical volumes, which were associated with cognitive deficits. The thalamus, nucleus accumbens, and putamen may serve as potential biomarkers for Parkinson disease–mild cognitive impairment. MCImild cognitive impairmentMDSMovement Disorder SocietyPDParkinson diseasePD-MCIParkinson disease with mild cognitive impairmentPD-NCIParkinson disease with no cognitive impairmentSDGMsubcortical deep gray matterSIENAXStructural Image Evaluation, with Normalization of Atrophy